Fine-tuning of functional and structural properties of Ca(II)-alginate beads containing artichoke waste extracts - Zazzali, Ignacio; Jaramillo, Gabriela; Gabilondo, Julieta; Peixoto Mallmann, Luana; Rodrigues, Eliseu; Perullini, Mercedes; Santagapita, Patricio R. (Elsevier, 2022)
Artichoke harvest waste is rich in phenolic compounds, which we retrieved with green extractions to exploit this otherwise undervalued material. Here, to protect these labile compounds, we encapsulated the extract into Ca(II)-alginate beads and optimized their physico-chemical and structural properties via response surface methodology. Moreover, we corroborated the carryover of predominant phenolic compounds from waste to bead via high-performance liquid chromatography coupled with diode-array detection and mass spectrometry (HPLC-DAD-MS). We found that maximum bioactive capacity is obtained at higher concentrations of alginate precursor and lower gel consolidation times and that strength, size, and roundness of the beads were influenced mainly by the alginate precursor concentration. Additionally, through small angle X-ray scattering we revealed a deep relationship between synthesis conditions and the microstructure of the gel, related to the crosslinking degree and ramification of the final arrangement, which in turn impacts its strength. We validated the model by running an optimal point of 2 min of gelling time and 2.25 % of alginate and obtaining satisfactory experimental errors for the parameters analyzed. This holistic approach enables modulation and bottom-up tuning of the structure of beads for advanced delivery applications.